Nafcillin versus cefazolin for the treatment of methicillin-susceptible Staphylococcus aureus bacteremia - Marguerite L. Monogue; Jessica K. Ortwine; Wenjing Wei; Khalid Eljaaly; Kavita P. Bhavan (Elsevier, 2018)
Background: Anti-staphylococcal penicillins have long been the first-line treatment option for methicillin-susceptible Staphylococcus aureus (MSSA) infections. Recent retrospective data comparing nafcillin and cefazolin report similar clinical efficacy despite concerns about high inoculum MSSA infections. Methods: This was a retrospective, non-inferiority, cohort study comparing treatment failure rates between nafcillin and cefazolin in patients with MSSA bacteremia from any source, other than meningitis. Multiple logistic regression was used to adjust for confounding variables. Results: A total of 142 patients were included in the study. The overall treatment failure rate among patients receiving cefazolin was non-inferior to nafcillin (11.3% versus 8.5%; 90% confidence interval −5.2% to 10.8%). Rates of adverse drug events were significantly higher in the nafcillin arm (19.7% versus 7%; p = 0.046). After adjustment for confounding variables, no difference between treatment groups was found in treatment failure (adjusted odds ratio (OR) = 1.2; 95% CI, 0.3-4.5), but nafcillin was associated with significantly higher nephrotoxicity (adjusted odds ratio (OR) = 5.4; 95% CI, 1.1-26.8). Conclusion: Cefazolin was associated with lower nephrotoxicity and similar treatment failure rates compared to nafcillin suggesting that cefazolin is an appealing first line agent for most MSSA bloodstream infections. Keywords: Nafcillin, Cefazolin, Methicillin-susceptible Staphylococcus aureus, MSSA, Bacteremia